Education of Children with Borderline Intellectual Functioning - Specificity and Areas of Support - Justyna Śmietańska (Maria Curie-Skłodowska University, Lublin, Poland, 2021)
Introduction A characteristic feature of each class in a public school is the presence of children with a borderline intellectual functioning. This article presents the specificity of the functioning of children with the above-mentioned intellectual potential. Evidence-based Facts The aforementioned group of pupils is accompanied by a number of different deficits and difficulties, both of a cognitive and educational nature, as well as of a social and emotional-motivational nature. Often the symptoms resulting from these developmental abnormalities are interpreted and identified in an inadequate, simplified and harmful way. Meanwhile, these children require special psychological and pedagogical support as well as adapting the requirements and teaching methods during their current cognitive work. Research Aim The article presents the specificity of the deficits, characterises the type of irregularities, both in the cognitive-educational, emotional-motivational and social spheres. Selected empirical research on this subject has been reviewed. The significance of this phenomenon was discussed in the context of the correct diagnosis and direction of the further didactic and educational process. Specific methodological guidelines have also been formulated that may be helpful for practitioners in their daily work with this group of pupils. Summary Pupils with borderline intellectual functioning constitute about a dozen or so percent of the population. Due to the reduced intellectual capacity, as a rule, they are accompanied by a number of difficulties. The basis for the individualisation of work and the selection of methods of support for pupils with the above-mentioned irregularities should be a reliable, correct diagnosis and ongoing monitoring of the difficulties.